Socio-Demographic Variables as Correlate to the Application and Use of Social Media in Informal Sector in Southwest Nigeria: A Gender Perspective: Social media use in the informal sector in Nigeria - Kolawole, Taiwo; Atere, Oluwole Akinyemi; Adeyemi, Olugbenga; Akingbe, Niyi (The Journal of Accounting and Management, 2021)
The descriptive study focused on the socio-demographic variables of men and women as a correlate to the adoption and use of social media in the informal sector in southwestern Nigeria. The study took place in the southwestern part of Nigeria which is made up of six states. Four out of the six states were purposively selected for this study they comprise Lagos, Oyo, Ondo and Ekiti states. A semi-structured questionnaire was designed to collect quantitative data for the study. A sample size of 200 respondents was selected in each state totaling 800 respondents using the convenience sampling technique. In all, 755 questionnaires were finally sorted and analysed for this study. The IBM SPSS version 21 was used to analysed the quantitative data. The findings revealed that 50.5% and 42.5% of male and female respectively have heard of social media, 2.6% men and 4.0% women heard about social media in less than 6 months while 31.7% men and 25.4% women heard about social media for over 6 years. The result of cross tabulation of age and social media use showed that 20.9% male and 14.6% female within age 15-25 years said yes, they use social media for business. In respect to religion, 41.2% male and 31.7% female who are Christians also said yes, they use social media for business. The educational qualification of the respondents indicated that all respondents were literate at different levels use social media for businesses even those who do not have formal education (0.3% men and 0.5% women) also use social media for their various business. On marital status, 28.6% of single but never marry men and 26.8% of married women said yes, they use social media for business and result for ethnicity revealed that among the Yoruba, 41.9% men and 37.8% women also use social media for business. The study concluded that none of the socio-demographic variables of people in the informal sector in southwestern Nigeria determine of application and use of social media to improve or boost their business to global standard except ethnicity of the people which may be misinterpreted for the rate of cybercrime in Nigeria and globally.